ANJURAN BERPAKAIAN PUTIH DALAM NORMATIVITAS HADIS (Studi Takhrij al-Hadis dan Ma’ani al-Hadis) - Eko Zulfikar (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
This paper does a study of takhrij al-hadis on the hadith which speaks about the suggestion of wearing white. With a focus on heritage studies, the author traces all the traditions of the Prophet in the al-kutub al-tis’ah (nine main books of hadis). In understanding the hadith, this paper specifically examines ma’ani al-hadis with an ethical approach as well as intertextuality data analysis. Thus, it was found that the recommended traditions of white dress were considered valid and could be used as evidence, because they had fulfilled the requirements and rules of the hadith. As for the understanding of the hadith, besides the white clothes the Prophet strongly recommends that the editorial form is qauly (sayings), this color also contains a more sacred and better ethical value so that it requires those who wear it to behave and have personality according to the values contained in white that - good, clean, and holy.